Coefficient Convexity of Divisors of $x^{n}-1$ - Decker, Andreas; Moree, Pieter (Sarajevo Journal of Mathematics, 2024)
We say a polynomial $f\in {\mathbb Z}[x]$ is strongly coefficient convex if the set of coefficients of $f$ consists of consecutive integers only. We establish various results suggesting that the divisors of $x^n-1$ that are in ${\mathbb Z}[x]$ have the tendency to be strongly coefficient convex and have small coefficients. The case where $n=p^2q$ with $p$ and $q$ primes is studied in detail. 2010 Mathematics Subject Classification. 11B83, 11C08